Hypertriglyceridemia Is Associated with Reduced Leukoaraiosis Severity in Patients with a Small Vessel Stroke - Daqiang Ke; Feng Zhou; Hui Liang; Yang Xu; Haiyan Lou (Behavioural Neurology)
Intracranial hemorrhage or microbleeds and leukoaraiosis have an overlap in biology. Hyperlipidemia may reduce the risk of ICH or cerebral microbleeds; studies focusing on the relationship between different lipid profiles and severity of periventricular hyperintensities (PVH) and subcortical white matter lesions (SWMLs) in the cerebral small vessel disease are limited. Methods. Patients with recent first lacunar infarct were recruited. PVH and SWMLs were accessed on MRI with the Fazekas scale, and lipid levels were measured. Univariate and multivariable regression analyses were used to assess the relation between different lipid profiles and severity of PVH and SWMLs. Results. In univariate analyses, advancing age was correlated with increasing severity of leukoaraiosis (P<0.001). There was an inverse relationship between hypertriglyceridemia (hyper-TG) (≥1.7 mmol/l) and severity of leukoaraiosis (P<0.05). In the multivariable analysis, after controlling for age, sex, and significant risk factors in the univariate and age-adjusted analyses, hyper-TG demonstrated a protective effect on the severity of PVH and SWMLs (P<0.05). Higher total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were not associated with leukoaraiosis. Conclusions. Hyper-TG is associated with the severity of leukoaraiosis independent of other risk factors, and it might be a protective role in cerebral small vessel disease.